Service performance and ISO 9000: Exploring the Academic Library Users Satisfaction (ALUS) model as proxy for university quality level - Taib, Che Azlan; Warokka, Ari (2011)
This study aims to examine a first-order CFA model designed to test the multi-facet of academic library user satisfaction theoretical construct. Particularly, the study aims to test the hypothesis that ALUS (Academic Library Users Satisfaction) is a multidimensional construct consisted of five factors - quality of staff services, quality of electronic services, suitability of library services, availability of library physical, and library service accessibility.This study involved 3605 samples.The data accessed across multiple groups of library user's background.The reliability tests displayed the internal consistencies of the five factors were satisfactorily (a=0.94).To evaluate the extent to which the hypothesized model fitted or in other word,adequately described the sample data, the results showed that the GFI was 0.91, AGFI was 0.89, and the PGFI was 0.75. This result indicated that the model was highly goodness fit and all dimensional constructs supported the proposed theoretical model.